Role of CD11b/CD18 in the Process of Intoxication by the Adenylate Cyclase Toxin of Bordetella pertussis - Eby, Joshua C. (American Society for Microbiology, 2012)
The adenylate cyclase toxin (ACT) of Bordetella pertussis does not require a receptor to generate intracellular cyclic AMP (cAMP) in a broad range of cell types. To intoxicate cells, ACT binds to the cell surface, translocates its catalytic domain across the cell membrane, and converts intracellular ATP to cAMP. In cells that express the integrin CD11b/CD18 (CR3), ACT is more potent than in CR3-negative cells. We find, however, that the maximum levels of cAMP accumulation inside CR3-positive and -negative cells are comparable. To better understand how CR3 affects the generation of cAMP, we used Chinese hamster ovary and K562 cells transfected to express CR3 and examined the steps in intoxication in the presence and absence of the integrin. The binding of ACT to cells is greater in CR3-expressing cells at all concentrations of ACT, and translocation of the catalytic domain is enhanced by CR3 expression, with ∼80% of ACT molecules translocating their catalytic domain in CR3-positive cells but only 25% in CR3-negative cells. Once in the cytosol, the unregulated catalytic domain converts ATP to cAMP, and at ACT concentrations >1,000 ng/ml, the intracellular ATP concentration is <5% of that in untreated cells, regardless of CR3 expression. This depletion of ATP prevents further production of cAMP, despite the CR3-mediated enhancement of binding and translocation. In addition to characterizing the effects of CR3 on the actions of ACT, these data show that ATP consumption is yet another concentration-dependent activity of ACT that must be considered when studying how ACT affects target cells.